Microstructure, dielectric and ferroelectric properties of CaCu3-xZnxTi4-xCexO12 ceramics prepared via semi-wet route - Gond A.K.; Kumar A.; Ansari A.A.; Kumar S.; Kumar S.; Gupta A.N.; Kumar A.; Lee Y.; Mandal K.; Shekher H.; Singh L. (My University, 2025)
In this work, the effect of bi-substitution of Zn and Ce at Cu and Ti sites on microstructure and dielectric properties of CaCu3Ti4O12 ceramics was investigated. The doped CaCu3-xZnxTi4-xCexO12 (CCZTC-x) powders (where x = 0.1, 0.2 and 0.3) were successfully synthesized via semi-wet route and the corresponding ceramics were obtained by sintering at 950°C for 14 h in air. The presence of major cubic CaCu3Ti4O12 phase along with minor secondary CuO phase was observed by X-ray diffraction analysis. Scanning electron microscopy analyses confirmed microstructure consisting of cubic-shaped grains and grain sizes of 0.76, 0.87 and 0.98 μm, for the ceramics with x = 0.1, 0.2 and 0.3, respectively. The high value of relative dielectric constant of 1500 at 100Hz was found for the sample with x = 0.3, which may be regarded as having semiconducting grains surrounded by insulating grain boundaries. In addition, conductivity of the sintered samples decreases with doping concentrations and the activation energies of the samples with x = 0.1, 0.2 and 0.3 are 0.93, 0.76 and 0.74 eV, respectively. © 2024 University of Novi Sad, Faculty of Technology. All rights reserved.